Satu kajian tentang tingkah laku agresif di kalangan pelajar Universiti Malaysia Sarawak - Shahreen, Alias. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The main purpose of this study was to study the types and characteristics of aggression among University Malaysia Sarawak (UNIMAS) students. T his study also aimed to see the student of U NIMAS perception and opinion regarding aggression. The Aggression Questionnaire by Arnold H. Buss and Mark Perry in 1992 and Aggression Inventory by Brian A. Glaude in 1991 were applied to examine about the types and characteristics of aggression among UNI MAS students. There were four (4) types of aggression which are physical aggression, verbal aggression, anger , and hostil ity . There are also four (4) characteristics of aggression which are physical aggression, verbal aggression, impulsive or impatient , an d avoid. About a hundred and twelve respondents among UNIMAS students were chosen randomly as samples for this research. The design of this study was formed based on the quantitative research and used Aggressive Q uestionnaire and Aggression Inventory to co llect the data needed for this research. In this study, the female students were founded more aggressive in term of physical ( M = 23.59) and hostility ( M = 21.83) for the aggression questionnaire than male students and also have higher scores than male stu dents in the impulsive or impatient ( M = 2.8990) and avoid ( M = 3.4819) characteristics. However, the result of the study show ed that there were no significant differences between gender and the types and characteristics of aggression. The result also show s that there were no significant correlation between age with the types and characteristics of aggression. As for t he result of the perception and opinion section, the researcher found that most of the respondent aware the seriousn ess of the aggression pro blem and know a little bit about the studied aggression. The respondent also stated that there were a lot of ways that can be used to barricade the problem from ge tting worse and the barricading has to be started from the sources of the problem which are t he home and environment and also involving the parents, family, friends , and school.